(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
This research paper discusses the stages in the development of the application software named Engineering Science App. The main purpose of its development is to establish an online platform that can facilitate the implementation process of the lab work for students taking the Engineering Science course (DBS10012). The application is designed to cater for both online and face-to-face learning modes, is compatible with both Android and iOS platforms, is easily shared, and is user-friendly, especially for first-time users. The application is developed to be platform-independent, thus making it accessible from any type of device. The Engineering Science App was designed as an interactive application that guides students through the correct steps to perform the experiments and produce comprehensive lab reports. The development of the application focuses on the management of lab reports by students as well as the lecturers monitoring of the on-going progress to ensure a meaningful and quality output is achieved as the product. The implementation of engineering science lab work has been rather challenging in the absence of a centralized management system in place. In this study, we have succeeded in building application software that proves to be effective based on the high scores achieved on the user satisfaction survey. The results show that the Engineering Science App has significantly improved the Engineering Science lab work implementation process.